2010
DOI: 10.1111/j.1600-0560.2009.01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined bullous pemphigoid and pemphigus vulgaris in an 18‐year‐old female

Abstract: We present a case of an 18-year-old female with clinical, histological and immunopathological features of overlapping pemphigus vulgaris and bullous pemphigoid. This case is unique both in the context of the distinctive hybrid nature of the bullous disorder and the young age of onset. An initial biopsy showed a combined pemphigus pattern histologically and a dominant pemphigoid pattern by immunofluorescence, hence posing a diagnostic conundrum. A subsequent biopsy however confirmed a combined pemphigus and pem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our data support this concept of autoimmune diathesis in PV, as patients have a higher frequency of autoimmune disease in general relative to the U.S. population. Previous studies have proposed an association between PV and a number of autoimmune diseases . However, there is no consensus as to whether particular autoimmune diseases are more commonly associated with PV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data support this concept of autoimmune diathesis in PV, as patients have a higher frequency of autoimmune disease in general relative to the U.S. population. Previous studies have proposed an association between PV and a number of autoimmune diseases . However, there is no consensus as to whether particular autoimmune diseases are more commonly associated with PV.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports in the literature concerning the association and clustering between different autoimmune diseases . Several case reports and studies have reported associations between PV and a number of individual autoimmune diseases . However, there is a lack of consensus as to whether these are sporadic disease associations or part of a pattern of concomitant autoimmune diseases that may form distinct clusters.…”
mentioning
confidence: 99%
“…Adolescence is a hormonally driven period of development during which physiologic, cognitive, and psychosocial functioning changes foster the transition from childhood to adulthood. It is divided into three phases: early (10-13 years of age), middle (14)(15)(16)(17), and late adolescence (18)(19)(20)(21). 3 All published data were reviewed according to these phases of adolescence.…”
Section: Definitionsmentioning
confidence: 99%
“…Further, few cases with antibodies to the intercellular space (ICS) and basement membrane zone (BMZ) have been reported, [1][2][3] especially with both immunoglobulin (Ig)G and IgA antibodies. Further, few cases with antibodies to the intercellular space (ICS) and basement membrane zone (BMZ) have been reported, [1][2][3] especially with both immunoglobulin (Ig)G and IgA antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Pemphigus and pemphigoid are two distinct groups of autoimmune blistering diseases, and both diseases rarely occur at the same time in the same patient. Further, few cases with antibodies to the intercellular space (ICS) and basement membrane zone (BMZ) have been reported, [1][2][3] especially with both immunoglobulin (Ig)G and IgA antibodies. 4,5 In this report, we describe a highly rare case of pemphigus vulgaris (PV) with IgG and IgA bound to both the ICS and BMZ.…”
Section: Introductionmentioning
confidence: 99%